Fabrication and characterization of DDAB/PLA-alginate composite microcapsules as single-shot vaccine. Issue 24 (11th April 2018) - Yang, Meiyang; Yang, Tingyuan; Jia, Jilei; Lu, Ting; Wang, Hailin; Yan, Xueying; Wang, Lianyan; Yu, Lian; Zhao, Yue
Abstract : The most effective method to reduce chronic hepatitis B virus infection is the universal implementation of vaccination. Abstract : The most effective method to reduce chronic hepatitis B virus infection is the universal implementation of vaccination. The commercial aluminum-based vaccines need multiple-injection protocols for complete protection resulting in poor compliance in developing countries. It is necessary to develop single-shot vaccine formulations. In this study, novel antigen-loaded DDAB/PLA (didodecyldimethylammonium bromide/poly(lactic acid)) nanoparticles (NPs)-alginate composite microcapsules were developed as a single-shot vaccine. The hepatitis B surface antigen (HBsAg)-loaded DDAB/PLA NPs were successfully encapsulated into alginate microcapsules by a modified spray-solidification technique. The response surface method was applied to optimize the preparation parameters employing encapsulation efficiency of HBsAg and particle size of microcapsules as response variables. The antigen-loaded DDAB/PLA NPs-alginate composite microcapsules were prepared under these optimal conditions: the size of composite microcapsules was 24.25 μm, the Span value was 1.627, and the encapsulation efficiency of HBsAg was 68.4%. The obtained microcapsules were spherical gel microparticles with excellent dispersity and narrow size distributions. In vitro release profile indicated a slow release rate of encapsulated HBsAg especially in phosphate buffered saline solution. The microcapsules showed little toxicity in vivo . This vaccine delivery system could induce stronger immune responses by a single shot, which exhibited much higher cytokine secretion levels closely related to cellular immunity and comparable IgG titers to the traditional aluminum-adjuvanted vaccine with three shots.